Peningkatan Pengetahuan Tentang Bahaya Dan Penatalaksanaan Hipertensi Pada Usia Dewasa - Endang Yuswatiningsih; Ifa Nofalia; Inayatur Rosyidah; Agustina Maunaturrohmah; Anita Rahmawati (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Hypertension is a non-communicable disease that is a leading cause of morbidity and mortality worldwide. Lack of public knowledge about the risks and management of hypertension leads to low awareness of blood pressure control. This community service activity aims to improve adults' understanding of the risks and management of hypertension. This community service activity was conducted in Dukuhlopo Hamlet, Jombang, and was attended by 53 participants who had risk factors for hypertension or had been diagnosed with hypertension. The methods used included interactive counseling, discussions, and blood pressure screening. The results of the community service showed that before the counseling, almost half of the participants had insufficient knowledge (36%). After the health education, the majority of participants had good knowledge (55%). The results showed an increase in participants' knowledge after the health education. Health education is effective in increasing public awareness and understanding of the importance of hypertension control to prevent long-term complications